THE INFLUENCE OF LEADERSHIP AND WORK QUALITY ON EMPLOYEE PERFORMANCE WITH EMPLOYEE RETENTION AS AN INTERVENING AT ASN ARMY HOSPITAL TK III DR. REKSODIWIRYO PADANG - Jaya Subrata, I Nyoman; Rizky, M. Chaerul (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
This research was conducted in order to see the influence of leadership and work quality on employee performance with employee retention as an intervention at the Asn Army Hospital Tk Iii Dr Reksodiwiryo Padang. With this research the researchers conducted this research on Jl. Dr. Wahidin No.1, Ganting Parak Gadang, Padang Timur District, Padang City, West Sumatra 25132. This research uses quantitative research, and uses primary data sources, the population of this research is 75 entire employees and the sample used is the population, so it uses a sampling technique bored for research, data collection used the questionnaire distribution method and used the Phat analysis model as the research model and used the Smart PLS version 3 tool to calculate research results. The results of this research are as follows: Leadership has a positive and insignificant effect on employee performance with an original sample value of 0.059 and an ap value of 0.725. Work Quality has a positive and insignificant effect on Employee Retention with an original sample value of 0.123 and ap value of 0.538. Work Quality has a positive and insignificant effect on employee performance with an original sample value of 0.126 and ap value of 0.289. Employee retention has a positive and significant effect on employee performance with a value of 0.783 and a value of 0.000. Leadership has a positive and significant effect on employee retention with an original sample value of 0.841 and ap value of 0.000. Leadership influences employee performance through employee retention positively and significantly with an original sample value of 0.658 and ap value of 0.000. Work Quality has an indirect and insignificant effect on Employee Performance through Employee Retention, with an original sample value of 0.096 and ap value of 0.540.